ANALISIS PENYUSUNAN AGENDA KEBIJAKAN PUBLIK (STUDI KAJIAN AGENDA PENYUSUNAN KEBIJAKAN PENYELESAIAN PELANGGARAN RTRW OLEH INDUSTRI CV. EVERGREEN INDOGARMENT) - Ratih Indah Puspita; Muhammad Adnan; Priyatno Harsasto (Journal of Politic and Government Studies, 2016)
This research is having purpose to analyze the settlement process of UrbanLand Use Plan (RTRW) violation conducted by CV. Evergreen IndogarmentTuntang, by using policy agenda setting analysis. This research analyzes interactionsbetween parties involved in the violation settlement process. This research is usingmethod of qualitative. In order to collect primary data, this research is using interviewapproach. The interview performed to two key informants, they are Mr. M. Mashadi,S.IP as Head of BPMPPTSP Capital Placement Division and Mr. Suharnoto, S.Sos,MM, as Head of Industrial Relationship Development of DINSOSNAKERTRANS.Furthermore, to collect additional information from surrounding community, thisresearch is using Snowball method as well as collecting secondary information frommass media and other bibliographical resources.The result of this research shows that the violation conducted by CV.Evergreen Indogarment has had achieved backed up from politicians, through thispolitical stream, CV. Evergreen gained politician backing by establishing coalition inorder to forge their violation. By generating group of people consists of CommunityOrganization of Sub-district of Tuntang, and labor to sign petition to be addressed toRegent of Semarang Regency. It caused difficulties for regional government toperform law enforcement to the factory despite of the violation against Regional Lawand Regulation they have conducted, the factory is still operating until present.As for the conclusion, the three streams namely problem stream, policystream, agenda setting through political stream, are the dominant aspects in thepredicament of RTRW Violation Settlement Policy conducted by CV. EvergreenIndogarment.